Immature Plasma Cell Myeloma Mimics Metastatic Renal Cell Carcinoma on 18F-PSMA-1007 PET/CT Due to Endothelial PSMA-Expression - Lena M. Mittlmeier; Stephan T. Ledderose; Melanie Schott; Matthias Brendel; Leonie Beyer; Sebastian Theurich; Doris Mayr; Christoph Walz; Wolfgang G. Kunz; Jens Ricke; Peter Bartenstein; Harun Ilhan; et al. (Diagnostics, 2021)
We present a 71-year-old female patient who underwent 18F-PSMA-1007 PET/CT for suspected metastatic renal cell carcinoma (RCC), as RCC also shows high PSMA-expression in tumor neovascularization. 18F-PSMA-1007 PET/CT showed a high PSMA-avidity in the renal tumor, enlarged intra-abdominal and mediastinal lymph nodes. Moreover, PSMA-positive pleural, pulmonal and osseous lesions were found. However, histopathology revealed an immature plasma cell myeloma with an endothelial PSMA-expression of the neovasculature. This case illustrates the increased PSMA-avidity in multiple myeloma and highlights PSMA as a potential theragnostic target in multiple myeloma. For clinical routine, lymphatic diseases such as extramedullary myeloma should be considered as differential diagnosis in PSMA-avid renal masses on PET/CT.